Plantar Fasciitis—A Comparison of Treatment with Intralesional Steroids versus Platelet-Rich Plasma - Acosta Olivo, Carlos Alberto; Elizondo Rodríguez, Jorge Alberto; Lopez Cavazos, Ricardo; Vílchez Cavazos, José Félix; Simental Mendía, Mario Alberto; Mendoza Lemus, Oscar Fernando (American Podiatric Medical Association, 2017)
Background: Many treatment options for plantar fasciitis currently exist, some with great success in pain relief. The objective of our study was to compare the use of intralesional steroids with platelet-rich plasma (PRP), using pain scales and functional evaluation, in patients with plantar fasciitis who did not respond to conservative treatment. Methods: A controlled, randomized, blinded clinical assay was performed. Patients were assigned to one of the two groups by selecting a sealed envelope. The steroid treatment group received 8 mg of dexamethasone plus 2 mL of lidocaine as a local anesthetic. The PRP treatment group received 3 mL of PRP activated with 0.45 mL of 10% calcium gluconate. All of the patients were evaluated at the beginning of the study, and at 2, 4, 8, 12, and 16 weeks post-treatment with the Visual Analog Scale (VAS), Foot and Ankle Disability Index (FADI), and American Orthopedic Foot and Ankle Society (AOFAS) scale. Results: The right foot was the most frequently affected foot (63%). The average age of the patients was 44.8 years (range, 24–61 years). All scales used (VAS, FADI and AOFAS) showed that the difference was not statistically signiﬁcant between the two groups. Conclusions: We can conclude that the use of PRP is an effective treatment method for patients with plantar fasciitis who do not respond to conservative treatment because PRP demonstrates an efﬁcacy equal to that of steroids. However, the cost and the time for preparation the PRP are two of the disadvantages of this treatment. (J Am Podiatr Med Assoc 107(6): 490-496, 2017)